Strategy Sustainable Innovation in the Development of Oyster Mushroom Cultivation to Enhance the Financial Resilience and Competitiveness of MSMEs - Yundari Monica Putri; Nevi Fitriani; Ahmad Soleh; Karona Cahya Susena (Universitas Dehasen Bengkulu, 2026)
This study compares sustainable innovation strategies, financial resilience, and competitiveness of two oyster mushroom farming businesses in Bengkulu, namely Dua Bersaudara and Meranti 4. A qualitative method with a comparative study approach was conducted through interviews and field observations. Results show Dua Bersaudara excels in modern production technology, while Meranti 4 is stronger in product diversification and digital marketing. Both businesses have structured financial management supporting financial resilience. The combination of technical innovation and digital marketing strengthens the competitiveness of oyster mushroom SMEs in Bengkulu.